Kondisi Sosial Budaya Nelayan Tradisional Dan Teknis Dalam Penggunaan Pancing Ulur (Hand Line) Di Dok IX Kelurahan Tanjung Ria Kota Jayapura - Gabriela O Karisoh; Lolita Tuhumena; Nicea Roona Paranoan; Efray Wanimbo; Basa T. Rumahorbo; Jeirel Wattilete (Universitas Pattimura, 2025)
Jayapura City is a coastal area that has the potential of marine resources, making it the center of economic activity for fishermen. The fishermen who live in Dock IX consist of two tribes, namely Serui and Buton, who have long been fishing in the waters of Jayapura. The culture of fishermen from both tribes is closely related to an orientation towards the sea. However, this needs to be balanced with the use of environmentally friendly fishing gear so that in the future, the sustainability of fishery resources, especially Yellowfin Tuna (Thunnus albacares), can be maintained. Therefore, it is necessary to understand the fishing gear used in the fishing process and the socio-cultural conditions of traditional fishermen in fishing using handlines. Primary and secondary data collection was conducted from March to May 2025 at Dock IX, Tanjung Ria Village, Jayapura City. The social conditions of fishermen were observed in terms of age, education, length of time working as fishermen, and number of dependents in Dok IX, Tanjung Ria Village, Jayapura City. From a cultural perspective, the Buton tribe does not catch fish (as it is not fishing season), so they offer sacrifices by feeding the sea. They believe that by feeding the sea, they will catch a lot of fish. In contrast, the Serui community does not perform rituals (customs) to make offerings in the process of catching fish. They use fiberglass boats, Yamaha engines with a capacity of 15 horsepower, and fish in the waters of Jayapura City, Pasir 6, Papua New Guinea, and even the waters of Sarmi Regency.